2017
DOI: 10.1007/s11524-017-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Parents and School-Functioning of Adolescents: Results from the World Trade Center Registry

Abstract: Poor school-functioning can be indicative of parent and adolescent mental health and adolescent behavior problems. This study examined 472 adolescents enrolled in the World Trade Center (WTC) Health Registry, with a two-step path analysis, using regression-based models, to unravel the relationships between parent and adolescent mental health, adolescent behavior problems, and adolescent unmet healthcare need (UHCN) on the outcome school-functioning. WTC exposure was associated with UHCN and parental mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…7,8 This can be associated with undesirable mental health that affects their level of functionality 9 and for many it impacts on educational achievement as well as the total health of adolescents, thereby having a substantial effect on opportunities in adult life. [10][11][12] A study done among adolescent students in Canada showed that 35.1% suffered from psychological distress which was significantly higher than any other sector of the general population. 7 Furthermore, 7.6% of students in California, 13 40.1% of students in China, 14 54% of students in Saudi Arabia, 15 64.7% of students in Indonesia, 16 20.8% of students in India 17 and 41.7% of students in Egypt 18 experienced psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 This can be associated with undesirable mental health that affects their level of functionality 9 and for many it impacts on educational achievement as well as the total health of adolescents, thereby having a substantial effect on opportunities in adult life. [10][11][12] A study done among adolescent students in Canada showed that 35.1% suffered from psychological distress which was significantly higher than any other sector of the general population. 7 Furthermore, 7.6% of students in California, 13 40.1% of students in China, 14 54% of students in Saudi Arabia, 15 64.7% of students in Indonesia, 16 20.8% of students in India 17 and 41.7% of students in Egypt 18 experienced psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the consequences of “single-incident traumas,” such as Hurricane Katrina, the World Trade Center terrorist attacks on September 11, 2001, and school shootings, or have evaluated the consequences using longitudinal data. Literature suggests that exposure as a child to the events of September 11, 2001, such as being caught in the dust cloud, witnessing horrific events, and having a family member killed in the attacks have been associated with poor outcomes as an adolescent including, substance use (19, 20), poor school-functioning (19, 21), and behavioral problems (22, 23). However, there is a paucity of research on the extent to which the effects of these adolescent behavior problems related to a single-incident trauma in childhood impact early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the results of the current study, Mann et al found that adolescents of parents with 9/11 related PTSD were at an increased risk for behavioral difficulties, specifically peer problems, and emotional symptoms. Additionally, Gargano et al found a significant association between WTC responder mental health and their child's mental health, behavioral problems, and school performance. WTC responder children largely had poor school functioning, including both cognitive traits (language and literacy skills) and non‐cognitive (social skills and self‐control strategies).…”
Section: Discussionmentioning
confidence: 99%